Nanoscopic Structural Fluctuations of Disassembling Microtubules Revealed by Label-Free Super-Resolution Microscopy - Vala, Milan; Bujak, Łukasz; García Marín, Antonio; Holanová, Kristýna; Henrichs, Verena; Braun, Marcus; Lánský, Zdeněk; Piliarik, Marek (Small methods, 2021)
Microtubules are cytoskeletal polymers of tubulin dimers assembled into protofilaments that constitute nanotubes undergoing periods of assembly and disassembly. Static electron micrographs suggest a structural transition of straight protofilaments into curved ones occurring at the tips of disassembling microtubules. However, these structural transitions have never been observed and the process of microtubule disassembly thus remains unclear. Here, label-free optical microscopy capable of selective imaging of the transient structural changes of protofilaments at the tip of a disassembling microtubule is introduced. Upon induced disassembly, the transition of ordered protofilaments into a disordered conformation is resolved at the tip of the microtubule. Imaging the unbinding of individual tubulin oligomers from the microtubule tip reveals transient pauses and relapses in the disassembly, concurrent with increased organization of protofilament segments at the microtubule tip. These findings show that microtubule disassembly is a discrete process and suggest a stochastic mechanism of switching from the disassembly to the assembly phase.
Keywords: Polymers; Microtubules; dynamic instability; microtubules; super-resolution microscopy; Protein Conformation; Microscopy; tubulin; Tubulin; polymery; mikroskopie; konformace proteinů; iSCAT; mikrotubuly; scattering anisotropy